Fly Guy presents : firefighters - Arnold, Tedd. (New York : Scholastic Inc., 2014)
Buzz and Fly Guy visit the firehouse, where they learn facts about firefighters, fire trucks, and fire safety.
3.2
K-3
610L
N
Keywords: Fire fighters -- Juvenile literature; Fire fighters; Fire extinction; Readers (Elementary)